NtrC-dependent control of exopolysaccharide synthesis and motility in Burkholderia cenocepacia H111. - Yilei Liu; Martina Lardi; Alessandro Pedrioli; Leo Eberl; Gabriella Pessi (PLoS ONE)
Burkholderia cenocepacia is a versatile opportunistic pathogen that survives in a wide variety of environments, which can be limited in nutrients such as nitrogen. We have previously shown that the sigma factor σ54 is involved in the control of nitrogen assimilation and virulence in B. cenocepacia H111. In this work, we investigated the role of the σ54 enhancer binding protein NtrC in response to nitrogen limitation and in the pathogenicity of H111. Of 95 alternative nitrogen sources tested the ntrC showed defects in the utilisation of nitrate, urea, L-citrulline, acetamide, DL-lactamide, allantoin and parabanic acid. RNA-Seq and phenotypic analyses of an ntrC mutant strain showed that NtrC positively regulates two important phenotypic traits: exopolysaccharide (EPS) production and motility. However, the ntrC mutant was not attenuated in C. elegans virulence.